Management of Anaphylactic Reactions in Patients Suspected of Kounis Syndrome with Severe Cardiovascular Disorders - Aryawan Suryakusuma, Anton; Suardamana, Ketut (Jurnal KESANS : Kesehatan dan Sains, 2024)
Kounis syndrome (KS) is a hypersensitivity coronary disorder induced by various conditions, drugs, environmental exposures, foods, and coronary stents. Allergic, hypersensitivity, anaphylactic and anaphylactoid reactions are associated with this syndrome. Vasospastic allergic angina, allergic myocardial infarction and stent thrombosis with occluding thrombus infiltrated by eosinophils and/or mast cells constitute are the three reported, so far, variants of this syndrome. Its etiology is continuously increasing. Kounis syndrome is a ubiquitous disease which represents a magnificent natural paradigm and nature’s own experiment in a final trigger pathway implicated in cases of coronary artery spasm and plaque rupture. These cells are not only present in the culprit region before plaque erosion or rupture but they release their contents just before an actual coronary event. Therefore, awareness of etiology, epidemiology, pathogenesis, and clinical manifestations seems to be important for its prognosis, diagnosis, treatment, prevention